2001
DOI: 10.1677/joe.0.1710085
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin receptor expression in the epithelia and stroma of the rat mammary gland

Abstract: The importance of prolactin (PRL) in regulating growth and differentiation of the mammary gland is well known. However, it is not well established whether PRL acts solely on the mammary epithelia or if it can also directly affect the mammary stroma. To determine where PRL could exert its effects within the mammary gland, we investigated the levels of expression and the localization of the PRL receptor (PRLR) in the epithelia and stroma of the rat mammary gland at different physiological stages. For these studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…It is well established that many hormones, including GH, IGF-1 and PRL, are necessary for the growth and differentiation of the mammary gland (Camarillo et al 2001;Naylor et al 2003;Kleinberg and Ruan 2008). In the present study, it was found that dietary SV enhances lactation potential possibly due to improving serum GH, IGF-1 and PRL concentrations in dams (Table 3).…”
Section: Resultssupporting
confidence: 59%
“…It is well established that many hormones, including GH, IGF-1 and PRL, are necessary for the growth and differentiation of the mammary gland (Camarillo et al 2001;Naylor et al 2003;Kleinberg and Ruan 2008). In the present study, it was found that dietary SV enhances lactation potential possibly due to improving serum GH, IGF-1 and PRL concentrations in dams (Table 3).…”
Section: Resultssupporting
confidence: 59%
“…We used T-47D cells as a PRLR-expressing model system since the PRL response monitored by known target genes was not observed in other mammary cell lines, such as MCF-7, MCF-10A, and primary HMEC, probably due to low PRLR expression. The expression of the functional long form of the PRLR in the mammary gland of rat and mouse is temporally regulated, showing lactationassociated up-regulation (Camarillo et al, 2001;Mizoguchi et al, 1996). Although experimental data to confirm this in humans is lacking, T-47D cells serve as a model system to study PRL signaling in the human mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…MBP protein levels were normalized to actin to control for differences in protein loading. The murine PRLR long form (PRLR-L) protein bands were recognized in the molecular weight range previously described by others (Ling et al, 2000;Camarillo et al, 2001).…”
Section: Western Blottingmentioning
confidence: 99%